2013
DOI: 10.3168/jds.2012-6409
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis and biogenic amine buildup in high-pressure treated ovine milk blue-veined cheese

Abstract: Penicillium roqueforti plays an important role in the ripening of blue-veined cheeses, mostly due to lactic acid consumption and to its extracellular enzymes. The strong activity of P. roqueforti proteinases may bring about cheese over-ripening. Also, free amino acids at high concentrations serve as substrates for biogenic amine formation. Both facts result in shorter product shelf-life. To prevent over-ripening and buildup of biogenic amines, blue-veined cheeses made from pasteurized ovine milk were high-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
1
24
0
2
Order By: Relevance
“…The precursor amino acids may be naturally present in milk in a free state or be released from milk proteins by hydrolysis. Proteolytic activities leading to the formation of precursor amino acids in dairy products may result from different sources acting independently or in combination, such as: (a) proteolytic strains of microorganisms present in dairy products, (b) the milk‐native heat‐stable protease plasmin, (c) proteases used for coagulating milk in cheese‐making, and (d) other proteases liberated from somatic cells (Tsakalidou ; Calzada and others ). Subsequently, BA‐producing microorganisms will continue the formation process of BAs (Figure ), which are then released into the matrix of dairy products.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%
“…The precursor amino acids may be naturally present in milk in a free state or be released from milk proteins by hydrolysis. Proteolytic activities leading to the formation of precursor amino acids in dairy products may result from different sources acting independently or in combination, such as: (a) proteolytic strains of microorganisms present in dairy products, (b) the milk‐native heat‐stable protease plasmin, (c) proteases used for coagulating milk in cheese‐making, and (d) other proteases liberated from somatic cells (Tsakalidou ; Calzada and others ). Subsequently, BA‐producing microorganisms will continue the formation process of BAs (Figure ), which are then released into the matrix of dairy products.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%
“…High histamine levels in cheese can cause hypotension, urticaria, flushing and headaches, whereas high amounts of tyramine, tryptamine and phenylethylamine can induce migraine headache and hypertension. Furthermore, the presence and build up of some amines in cheese can be an index of inadequate manufacturing practices (Buň ková et al, 2010;Calzada, Del Olmo, Picon, Gaya, & Nuñez, 2013;EFSA, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors may also contribute to the formation of biogenic amines in cheese, such as milk quality, pH, salt concentration, water availability, temperature and duration of ripening and storage, starter and non-starter lactic acid bacteria, bacterial density and the presence of cofactors and amine catabolism (Galgano, Caruso, Condelli, & Favati, 2012;Pachlová, Bunka, Flasarová, Válková, & Bunková, 2012;Santos, Souza, Cerqueira, & Gloria, 2003;Spizzirri et al, 2013). It has been reported that conditions leading to accelerated or enhanced proteolysis can result in a significant increase in biogenic amines during the ripening of cheese (Buň ková et al, 2013;Calzada et al, 2013;FernandezGarcia, Tomillo, & Núñez, 1999;Leuschner, Kurihara, & Hammes, 1998;Loizzo et al, 2013;Redruello et al, 2013). It is well known that mastitis can affect the quality and enhance proteolysis in milk; however no information is available regarding its role in the formation and accumulation of biogenic amines in cheese.…”
Section: Introductionmentioning
confidence: 99%
“…W Republice Słowacji przyjęto limit do 200 mg/kg dla zawartości histaminy i tyraminy w rybach i produktach rybnych, w Turcji dopuszcza się w rybach poziom histaminy do 200 mg/100 g, a w winach do 10 mg/kg (8). Netherlands Institute for Dairy Research rekomenduje dla mięsa i produktów mięsnych limit dla histaminy 100-200 mg/ kg (5,6,13,28,29,32). El-Kosi i wsp.…”
Section: Artykuł Przeglądowy Reviewunclassified
“…W serach, szczególnie dojrzewających, podstawą osiągnięcia pełnej dojrzałości, czyli właściwych, charakterystycznych cech sensorycznych, są m.in. procesy proteolityczne (6,23,28,29). Proteoliza w serach jest skutkiem działania enzymów rodzimych mleka (np.…”
Section: Artykuł Przeglądowy Reviewunclassified